EFFECT OF DIFFERENT FEEDING SYSTEM ON PERFOEMANCE OF LACTATING MURRAH BUFFALOES - kumar, vijay (Indian Journal of Dairy Science, 2014)
The objective of this study was to compare the performance of lactating buffaloes under traditional feeding system and feeding of Total mixed ration. Eighteen lactating Murrah buffaloes were divided into three group in randomize block design (RBD).The roughage and concentrate was fed separately in T1 group. The animals in T2 and T3 were fed TMR of different composition. Diet of animals consists of paddy straw, green maize fodder and concentrate mixture. The mean DMI was similar in three groups (13.71, 13.12 and 13.36 kg/d). The digestibility of DM, OM, NDF and ADF was increased in both TMR fed group. The average daily milk yield was 6.27, 5.99 and 6.77 kg in T1, T2 and T3 respectively. The milk fat and total solids were higher (pâ‰¤0.05) in T2, while, and milk protein and SNF was higher (pâ‰¤0.05) in T3 group.